DETERMINANTS AND CONSEQUENCES OF FINANCIAL REPORTING QUALITY: A SYSTEMATIC LITERATURE REVIEW - Dewi, I Gusti Ayu Ratih Permata; Suartana, Wayan; Yasa, Gerianta; Budiartha, Ketut (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
This study aims to review and compile the corpus of literature on the quality of financial reporting. It provides a comprehensive study of fifty-four papers published between 2016 and 2023 on this topic. The study was retrieved from the databases of Scopus. This review also identifies gaps in the literature, some of which have opposing conclusions, looks at potential data sources for empirical researchers, and suggests directions for further research. The search for innovative and unexplored research subjects is driven by the need for novelty in the field. This study identifies the origins and consequences of high-quality financial reporting. The ramifications of agency difficulties—conflicts of interest between principal and agent—are further discussed in this article. The practical effect of IFRS is that it results in financial reporting that is more appealing to investors.